Assessment of the inhibitory mechanism of action for a yeast cell-based screening system targeting glycogen synthase kinase-3ß (GSK-3ß) - D.N.A.F. Abdul Aziz; Fauze Mahmud; Hasidah Mohd Sidek; Noor Embi; T.T. Andoh; Lee, Ping Chin (ANSInet, 2017)
Background and Objective: Glycogen Synthase Kinase-3 (GSK-3) is one of the prior targets for drug discovery due to its involvement in many cell signaling and metabolism. It has been implicated in several critical diseases such as diabetes, Alzheimer’s disease, cancer and inflammation. To date, many GSK-3 inhibitors have been identified and classified into different type such as inorganic atom, ATP competitive and non-ATP competitive types. Many laboratories worldwide are still actively screening for bioactive compounds for GSK-3 inhibitory activity using diverse screening systems. This study assessed an assay developed using a yeast cell-based system specifically targeting GSK-3β for preliminary screening and cost effectiveness. Methodology: In this study, the GSK-3 homologues in yeast (MCK1, MDS1, MRK1 and YOL128C) were knocked out and inserted with mammalian GSK-3β. In order to determine the inhibitory mechanism, known GSK-3β inhibitors were tested and evaluated. Results: The GSK-3β inhibitor I and staurosporine showed inhibition on GSK-3β activity at a concentration of 1 and 20 μg disc–1, respectively. Other known inhibitors, such as indirubin-3’-monoxime, kenpaullone, GSK-3 inhibitor IV and enzastaurin showed no detectable inhibition in this study. Conclusion: The GSK-3β inhibitor I and staurosporine interacted with the same amino acid on GSK-3β which is Cys199 while other inhibitors have no interactions with Cys199 as reported in docking study. This study suggests that this yeast cell-based system can be used to screen GSK-3β inhibitors that is targeting on Cys199 residue.